PROSPECTS OF PILGRIMAGE TOURISM DEVELOPMENT IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2023)
This article provides feedback on the goals of tourism development in Uzbekistan. In recent years, the work being done in our country to improve this area and their effectiveness have been analyzed. It also analyzes existing shortcomings in the field of tourism and provides suggestions for addressing them.